Study Of Lokan Clam Ecology And Conservation Strategies As A Source Of Science Learning On The Material Of Diversity of Living Things in the Agam River, Air Rami Village, Mukomuko Regency - Anatasia , Lola; Satria, Irwan; Putra, Erik Perdana (GHAITSA : Islamic Education Journal, 2021)
This study aims to address the problems surrounding the ecology of lokan clams around the Agam River, Air Rami Village, Mukomuko Regency. In addition, this study also aims to design science learning resources based on ecological studies and conservation strategies in the region. The research method used is exploratory descriptive with a qualitative approach. The results showed that the ecology of lokan clams around the Agam River, Air Rami Village, Mukomuko Regency is strongly influenced by factors such as temperature, pH, salinity, and water currents. To maintain the lokan clam population, a conservation strategy has been implemented by imposing a minimum size limit for lokan clams in the Agam River. It aims to preserve the population of lokan mussels in the region. However, this conservation strategy faces obstacles such as lack of village planning, budget constraints, lack of community knowledge, and lack of government attention to the Agam River. This obstacle affects efforts to preserve lokan clams in the Agam River. In an effort to convey information about the ecology of lokan clams and their conservation strategies, this study designed science learning resources in the form of poster media.